2014
DOI: 10.1063/1.4868975
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire photonic crystal waveguides for single-atom trapping and strong light-matter interactions

Abstract: We present a comprehensive study of dispersion-engineered nanowire photonic crystal waveguides suitable for experiments in quantum optics and atomic physics with optically trapped atoms. Detailed design methodology and specifications are provided, as are the processing steps used to create silicon nitride waveguides of low optical loss in the near-IR. Measurements of the waveguide optical properties and power-handling capability are also presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 35 publications
4
151
0
Order By: Relevance
“…We see that ARROWs and HCPC fibers offer a convenient combination of core size and propagating mode area for applications utilizing cold atomic ensembles, as well as reasonably low propagation losses. In particular, their hollow cores with diameters of~10 µm allow confinement of lasercooled atoms with conventional atom-trapping methods with negligible effects from surface forces [10,11]. While the propagating mode area of ∼ 10λ 2 in these waveguides is not ideal, as the probability of interaction between one photon and one atom is approximately λ 2 /A mode [1], the mode area is actually comparable to that of standard single-mode fibers.…”
Section: Figmentioning
confidence: 90%
“…We see that ARROWs and HCPC fibers offer a convenient combination of core size and propagating mode area for applications utilizing cold atomic ensembles, as well as reasonably low propagation losses. In particular, their hollow cores with diameters of~10 µm allow confinement of lasercooled atoms with conventional atom-trapping methods with negligible effects from surface forces [10,11]. While the propagating mode area of ∼ 10λ 2 in these waveguides is not ideal, as the probability of interaction between one photon and one atom is approximately λ 2 /A mode [1], the mode area is actually comparable to that of standard single-mode fibers.…”
Section: Figmentioning
confidence: 90%
“…However they have not been a major drawback for experiments. Also, the values of atom coupling to the nanofiber currently do not reach those recently seen in nanophotonic devices Yu et al (2014); Goban et al (2015); Hood et al (2016), but the entire parameter space for traps has yet to be explored, and improvements may be possible.…”
Section: Nanofiber Platformmentioning
confidence: 99%
“…However, these plasmonic devices have relatively low quality factors (less than 100) due to the radiative and absorption losses of the metal structures, making them inefficient in terms of input power (Bozhevolnyi et al 2006). Enhanced optical tweezers using photonic devices (Mandal et al 2010;Cai and Poon 2010;) such as microring resonators (Lin et al 2010;Crozier 2011, coupled nanobeam cavities (Renaut et al 2013), optical fibers (Liberale et al 2013) PhC waveguides (Yu et al 2014) and cavities (Van Leest and Caro 2013) have also been demonstrated. PhC resonators have high quality factors (Q $ 500-100,000) and enable enhancement and control of the profile of the field (Lin and Crozier 2011), but they have lower spatial confinement (typically 0.5-10 lm) compared to near field plasmonic optical traps, which produce field hotspots of $ tens of nanometers (Schuller et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They have been used in cutting edge research where small particles play a role. The applications of optical trapping include: the observation of the angular momentum of light (Yao and Padgett 2011), the transport of Bose-Einstein condensates (Gustavson et al 2001), the investigation of the DNA mechanics (Bustamante et al 2003), spectroscopy and sensing (Cetin et al 2011), cancer research (Cross et al 2007), nanofabrication (Pauzauskie et al 2006), tissue engineering (Kim et al 1999;Matsuda and Sugawara 1996), the manipulation of single proteins (Pang and Gordon 2012) and single atoms (Yu et al 2014) and study and manipulation of live cell dynamics in animals (Zhong et al 2013).…”
Section: Introductionmentioning
confidence: 99%